2019
DOI: 10.1021/acs.langmuir.9b01208
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-Responsive Behavior of PNiPAm Microgels under Interfacial Confinement

Abstract: The volume phase transition of microgels is one of the most paradigmatic examples of stimuliresponsiveness, enabling a collapse from a highly swollen microgel state into a densely coiled state by an external stimulus. Although well characterized in bulk, it remains unclear how the phase transition is affected by the presence of a confining interface. Here, we demonstrate that the temperature-induced volume phase transition of poly(N-isopropylacrylamide) microgels, conventionally considered an intrinsic molecul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
125
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(135 citation statements)
references
References 83 publications
(274 reference statements)
9
125
1
Order By: Relevance
“…Instead, there is no reported evidence of deswelling when microgels are compressed at the interface. This is again due to the dominant role of the surface tension which makes adsorbed microgels much less responsive to external stimuli [32,35]. In this way, their compression is simply associated with a smooth and monotonic decrease of their interparticle distance, as described experimentally in Ref.…”
Section: Multiparticle Dynamical Responsementioning
confidence: 82%
See 1 more Smart Citation
“…Instead, there is no reported evidence of deswelling when microgels are compressed at the interface. This is again due to the dominant role of the surface tension which makes adsorbed microgels much less responsive to external stimuli [32,35]. In this way, their compression is simply associated with a smooth and monotonic decrease of their interparticle distance, as described experimentally in Ref.…”
Section: Multiparticle Dynamical Responsementioning
confidence: 82%
“…So far, the effects that an interfacial confinement induces on such particles have been mainly limited to the study of their characteristic shape, and hence, to their structural arrangement at oil-water and air-water interfaces. These aspects have been widely investigated experimentally [30,31] and, more recently, also numerically [29,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the volume phase transition is strongly modified due to the presence of the interface. Recent experiments [50][51][52] have analyzed the volume phase transition at the interface and showed that the volume phase transition in the lateral direction is strongly hindered by the presence of the liquid interface. In addition, a hysteresis behaviour upon swelling and deswelling of microgels dependent on whether the microgels were deposited in the swollen or collapsed state was found.…”
Section: Introductionmentioning
confidence: 99%
“…They are also termed 'smart-', 'intelligent-', or 'environmentally sensitive' polymers. 2,[10][11][12][13][14] One important feature of this type of material is reversibility, i.e. the ability of the hydrogel to return to its initial state upon application of a counter-trigger.…”
Section: Introductionmentioning
confidence: 99%